Effect of Antioxidant Status and Oxidative Stress Products in Pre-menopausal Women after Treatment with Date Seed Powder (Phoenix dactylifera L.): A Study on Women in Indonesia - Saryono; Rahmawati, E.; Proverawati, A.; Hisni, D. (Pakistan Journal of Nutrition, 2017)
Background: Degenerative diseases have the highest death rates in the elderly and these rates begin to rise starting in the pre-menopausal period. One degenerative disease is caused by an increase in free radicals, which induce oxidative stress. Objective: This study aimed to examine the effects of date seed powder on the antioxidant status and oxidative damage in pre-menopausal women in Gununglurah Village, Banyumas, Indonesia. Methodology: Deglet noor dates were cleaned, sun-dried, roasted and mashed. The date powder was poured into boiling water (250 cc). The antioxidant status (superoxide dismutase (SOD), glutathione peroxidase (GPX) and vitamin E) and oxidative damage (malondialdehyde (MDA)) were measured in women pre and post-treatment with date seed powder (2.5 g) for 2 weeks. The sample size of this study was 31 pre-menopausal women. The data were analyzed using a paired t-test. Results: The MDA level was significantly decreased after date seed consumption (p